If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + -6) = 7x + -12 Reorder the terms: x(-6 + x) = 7x + -12 (-6 * x + x * x) = 7x + -12 (-6x + x2) = 7x + -12 Reorder the terms: -6x + x2 = -12 + 7x Solving -6x + x2 = -12 + 7x Solving for variable 'x'. Reorder the terms: 12 + -6x + -7x + x2 = -12 + 7x + 12 + -7x Combine like terms: -6x + -7x = -13x 12 + -13x + x2 = -12 + 7x + 12 + -7x Reorder the terms: 12 + -13x + x2 = -12 + 12 + 7x + -7x Combine like terms: -12 + 12 = 0 12 + -13x + x2 = 0 + 7x + -7x 12 + -13x + x2 = 7x + -7x Combine like terms: 7x + -7x = 0 12 + -13x + x2 = 0 Factor a trinomial. (1 + -1x)(12 + -1x) = 0Subproblem 1
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Subproblem 2
Set the factor '(12 + -1x)' equal to zero and attempt to solve: Simplifying 12 + -1x = 0 Solving 12 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -1x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -1x = 0 + -12 -1x = 0 + -12 Combine like terms: 0 + -12 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12Solution
x = {1, 12}
| 5a+3(268-a)=1084 | | 6.09=n+7.1 | | 6x-2=16x+3 | | 5x^2-15xy-20y^2= | | 3a+1.50a=511.50 | | k^2+11k+24=0 | | 4x^3-24x^2-49x+249=x-6 | | 2x-1=4x+15 | | x+450*8=372 | | =3+5+6 | | 2-[4x-(1-2x)]=9(x+4) | | x+2(3x-1)=6x-5 | | 20=m+4 | | 7.4=-2.7(z+3.2) | | -5a+3=a-9 | | 3X+6+8=9 | | n-(-5)=35 | | 20x^2-41xy+20y^2= | | f=5 | | 0.5(11.8-x)=-x-8.1 | | -8x+3=-21 | | n-5=35 | | p^2-4p-16=0 | | (x*0.4)+x=20 | | 440*X=2475 | | 3(2x-55)=35 | | y-6=4 | | 6x+2=5x+22 | | P^2-8=2p | | 4x-148=2x+556 | | 5x+2x-15=9 | | 3m+1=1 |